2022
DOI: 10.1080/13554794.2022.2125326
|View full text |Cite
|
Sign up to set email alerts
|

Better conversations: a language and communication intervention for aphasia in posterior cortical atrophy

Abstract: Posterior cortical atrophy (PCA) describes a neurodegenerative syndrome characterized by progressive difficulties in cortical visual and other posterior cortical functions consistent with parieto-occipital and occipito-temporal involvement. It is increasingly recognized that many patients develop difficulties with other aspects of daily living, in particular, with language and communication. We present a case emphasizing how language difficulties may emerge in PCA. Difficulties are interpreted as arising from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Whilst behavioural interventions designed to specifically address language impairment in PCA are not currently available, approaches devised for lvPPA [95] may have promise, with consideration of concurrent visual needs (e.g. tendency to miss eye gaze, small gestures and expressions) [96]. Anecdotally used high-tech approaches supporting communication include tablet devices allowing for video calls minimising need to navigate (e.g.…”
Section: Memory and Languagementioning
confidence: 99%
“…Whilst behavioural interventions designed to specifically address language impairment in PCA are not currently available, approaches devised for lvPPA [95] may have promise, with consideration of concurrent visual needs (e.g. tendency to miss eye gaze, small gestures and expressions) [96]. Anecdotally used high-tech approaches supporting communication include tablet devices allowing for video calls minimising need to navigate (e.g.…”
Section: Memory and Languagementioning
confidence: 99%
“…As an example, a communication function such as coherent and connected propositional speech is key to effective communication in English, Chinese or Turkish (etc) even though the specific linguistic vehicles may vary widely between languages. This in turn will potentially have far-reaching implications beyond the scope of PPA, extending to people living with other dementia types, who also have speech, language and Open communication such as Posterior Cortical Atrophy, 37 Frontotemporal Dementia, Young Onset Alzheimer's Disease, Typical Alzheimer's Disease and Lewy Body Dementia. 38…”
Section: Discussionmentioning
confidence: 99%
“…However, these patients can present with impairments affecting other cognitive domains or develop abnormalities in these other domains over time. Early anomia, reduced verbal fluency, trouble with sentence repetition, and slowed speech rate (i.e., features of the language variant of AD), as well as phonological errors, can occur in patients with the visual variant of AD ( Crutch et al, 2013 ; Tetzloff et al, 2021 ; Volkmer et al, 2022 ), and have been observed in 50% of patients ( Singh et al, 2023 ). These language features relate to overlapping neuroanatomical features, particularly with atrophy in the left temporoparietal regions in patients with the visual variant of AD ( Wicklund et al, 2013 ; Tetzloff et al, 2021 ).…”
Section: Clinical Overlap Across Atypical Ad Variantsmentioning
confidence: 99%
“…I would also argue that there lacks rationale for focusing on just one clinical variant (i.e., amnestic AD) for therapeutic treatment trials, and that all variants of AD should be included to capture the true clinical spectrum of AD. The high degree of clinical overlap in these AD patients should also be considered for appropriate tailoring of patient management strategies ( Volkmer et al, 2022 ).…”
Section: Clinical Overlap Across Atypical Ad Variantsmentioning
confidence: 99%